2005
DOI: 10.1002/eji.200425699
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell immunity against the human papillomavirus‐18 E6 transforming protein in healthy donors: identification of promiscuous naturally processed epitopes

Abstract: Infection by 'high-risk' human papillomaviruses (HPV) is associated with the development of neoplastic lesions. HPV-18 is responsible for a very aggressive form of cancer and poor survival. As for other HPV types, immune surveillance has probably a role in the control of the infection. However, very little is known on HPV-18 immunogenicity. CD4 + T cells from 16 healthy donors were tested ex vivo for reactivity to synthetic peptides corresponding to 3 sequences on the HPV-18 E6 transforming protein predicted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…By in vitro studies, we previously identified promiscuous HPV-18 E6 CD4 epitopes recognized by 18% of healthy donors (15). Similar frequencies were found in another study (16), in which no reactivity in cervical cancer patients was found.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…By in vitro studies, we previously identified promiscuous HPV-18 E6 CD4 epitopes recognized by 18% of healthy donors (15). Similar frequencies were found in another study (16), in which no reactivity in cervical cancer patients was found.…”
supporting
confidence: 76%
“…17. promiscuous HLA-DR binders, as previously described (15). Peptides corresponding to selected sequences were synthesized by the stepwise solidphase method as in Ref.…”
Section: Hpv Detection and Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + T cells were purified from total PBMCs and CBMCs by magnetic separation (Miltenyi Biotech) and cultured as described previously (27,28). Briefly, CD4 + T cells (5 Â 10 4 per well) were cultured in X-VIVO 15 medium (Biowhittaker) supplemented with 3% heatinactivated normal human serum (NHS), penicillin (100 units/mL), and streptomycin (50 Ag/mL; Biowhittaker; tissue culture medium) in the presence of irradiated CD4 + -depleted PBMCs as antigen-presenting cells (APC) at 1:3 ratio in 96-well plates in six replicates for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…ϩ -depleted PBMC as APC at a 1:3 ratio in 96-well plates in six replicates for each condition as described elsewhere (29). Stimuli were PHA (1 g/ml), as a positive control, CD4…”
Section: Cd4mentioning
confidence: 99%